Dietary Supplementation with Omega-3-PUFA-Rich Fish Oil Reduces Signs of Food Allergy in Ovalbumin-Sensitized Mice - Olívia Gonçalves de Matos; Sylvia Stella Amaral; Pedro Elias Marques Pereira da Silva; Denise Alves Perez; Débora Moreira Alvarenga; Adaliene Versiani Matos Ferreira; Jacqueline Alvarez-Leite; Gustavo Batista Menezes; Denise Carmona Cara (Clinical and Developmental Immunology)
We investigated the effect of dietary supplementation with n-3 PUFA (fish oil source) in an experimental model of food allergy. Mice were sensitized (allergic group) or not (nonallergic group) with OVA and were fed with OVA diet to induce allergy signals. Mice were fed with regular diet in which 7% of lipid content was provided by soybean (5% of n-3 PUFA) or fish (25% of n-3 PUFA) oil. Allergic group mice had increased serum levels of antiovalbumin IgE and IgG1 and changes in small intestine, characterized by an increased edema, number of rolling leukocytes in microcirculation, eosinophil infiltration, mucus production, and Paneth cell degranulation, in comparison to non-allergic group. All these inflammatory parameters were reduced in mice fed high-n-3-PUFA diet. Our data together suggest that diet supplementation with n-3 PUFA from fish oil may consist of a valid adjuvant in food allergy treatment.